Better together?: a social identity approach to psychological adjustment groups for people with multiple sclerosis - Smale, Kathryn (2016)
People with multiple sclerosis (MS) commonly experience psychological problems including anxiety and depression. Evidence indicates that psychological interventions based on cognitive behavioural principles can help improve mental health. Such interventions are often delivered in groups and a common assumption is that the social interaction afforded by a group format is beneficial. The aim of this thesis is to explore this assumption and, drawing on social identity theory, investigate why and for whom MS psychological adjustment interventions are effective (or not) when delivered in a group.